COMPARATIVE OF INHIBITORY EFFICIENCY OF LIGNIN EXTRACT OF NIPAH (Nypa fruticans Wurmb) PEEL AND FROND ON MILD STEEL IN HCl MEDIUM - Emriadi, Emriadi; Sartika, Hilda; Pradiwi, Nailatul Zahrah; Stiadi, Yeni (Tanjungpura University, 2025)
Lignin extract from nipah fruit skin and nipah frond (Nypa fruticans Wurmb) was effectively extracted and used as a corrosion inhibitor on mild steel samples. The corrosion inhibition efficiency of lignin extract in 1 N HCl solution was determined by the weight loss method and surface morphology analysis using an optical microscope. The measurement results showed that the highest efficiency was obtained at the concentration of lignin extract from fruit skin (ELBN) and nipah frond (ELPN) of 82.16 and 78.36%. The adsorption of lignin extract on the surface of mild steel follows the Langmuir isotherm adsorption and includes mixed adsorption leading to chemical adsorption.